Power consumption prediction for an intelligent air-cushion tracked vehicle: fuzzy expert system - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Aminanda, Yulfian (David Publishing, USA, 2010)
This paper describes the unique structure of an intelligent air-cushion system of a hybrid electrical air-cushion track vehicle working on swamp terrain. Fuzzy expert system (FES) is used in this study to control the swamp tracked vehicle’s intelligent air cushion system while it operates in the swamp peat. The system will be effective to control the intelligent air-cushion system with total power consumption (PC), cushion clearance height (CCH) and cushion pressure (CP). Ultrasonic displacement sensor, pull-in solenoid electromagnetic switch, pressure sensor, micro controller and battery pH sensor will be incorporated with the (FES) to investigate experimentally the PC, CCH and CP. In this study, we provide illustration how FES might play an important role in the prediction of power consumption of the vehicle’s intelligent air-cushion system. The mean relative error of actual and predicted values from the FES model on total power consumption is found as 10.63 %, which is found to be alomst equal to the acceptable limits of 10%. The goodness of fit of the prediction values from the FES model on PC is found as 0.97.